Ovarian Ectopic Pregnancy after Endometriomal Cyst Resection, Following In vitro Fertilization (IVF): A Rare Case Report - fsaneh Tehranian; Sepideh Nekuie; Maryam Razavi; Farahnaz Sadat Ahmadi (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Background: primary ectopic pregnancy (EP), with 0.001-0.013% incidence rate, is a very scarce obstetrical condition. Among EPs Ovarian EP is more rarely seen?  Case: We present a case of ovarian EP following In vitro fertilization in a patient with history of endometriosis and curettage. With a primary diagnosis of tubal EP, the patient underwent laparoscopy, during which ovarian pregnancy was revealed. This was later confirmed with pathological review of the specimen.  Conclusion: Ovarian EP constitutes 3% of all EPs. Diagnosis of this condition is extremely hard before surgery; therefore, laparoscopy is considered a reliable means of diagnosis. Moreover, women conceiving with IVF-embryo transfer have a higher risk of EP.